PERTIMBANGAN HAKIM MENJATUHKAN PIDANA TINDAK PIDANA PERSETUBUHAN KEPADA ANAK (Studi Putusan Nomor 3/Pid.Sus-Anak/2022/PN Wng) - Niko Edi Santoso; Itok Dwi Kurniawan (Sebelas Maret University, 2023)
This study aims to determine the appropriateness of the application of the law in the Wonogiri District Court Decision Number: 3/Pid.Sus-Anak/2022/PN Wng which in its decision imposed a prison sentence of 2 (two) years 6 (six) months and 1 (one) month of training work at the Wonogiri Detention Center for Children The perpetrators of child sexual intercourse which are carried out continuously are associated with Article 79 of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The research method used is normative legal research which is prescriptive and applied. Types of legal materials include primary and secondary legal materials. The legal material collection technique used was literature study, then the analysis technique used was the deductive syllogistic method, namely drawing conclusions based on the submission of the major premise linked to the minor premise. The results of the study show that the judge's considerations based on juridical and non-juridical considerations impose criminal sanctions in the crime of committing a child. is in accordance with Article 79 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.Keywords: Judge's Consideration; Intercourse; Child